Explaining the Methodological Components in Seyed Jafar Shahidi Religious Historiography - Yaghoub Panahi; Asghar Montazeralghaem; Mohammad Ali Chelongar (تاریخ نگری و تاریخ نگاری, 2021)
Beginning in the West after the development of methodology and theoretical results in history, scientific historiography promoted the insights and methods of historians. It established new principles for the history of research. Inspired by these developments, contemporary Iranian historians also created new scientific frameworks, including Seyed Jafar Shahidi. Despite his theological and traditional origins, he benefited from the recent achievements of history in the fields of research on Islamic history and the life history of Shiite Imams. The present study mainly aims to study and explain the principles of historiography in Shahidi’s works to find the components of his historiography and answer whether they can be considered methodological and scientific. As a Muslim and Shiite historiographer, Shahidi believes to be influenced by social changes and responding to personal concerns and modern needs. Away from clutter, delusions, and excesses, these efforts have led to a kind of “religious historiography” aimed at strengthening and promoting religion and morality. Shahidi’s historiography has important methodological components such as the scientific and critical modification of narratives, the attempt to historically and methodologically explain some ideological ideas, the relative use of approaches and foundations of other sciences to provide comprehensive analysis and critique of the views of some Muslim or Orientalist writers. Shahidi tried to apply the aforementioned principles scientifically and methodologically as a literary historiographer, with expressive literature based on interrogative dialogue with historical subjects. However, in some respects, he does not go beyond traditional descriptions and has a strong religious influence; he may be considered a “neocentrist” historiographer.